Emotional Intelligence: A Cornerstone of Effective Management Practice - Dr Javed Meraj; Osama Habib; Haji Ameen; Sajid Ali; Balach Khan (Review Journal of Social Psychology & Social Works, 2024)
This research examines how Emotional Intelligence influences the effectiveness of managers and local businesses in Lasbela, Balochistan. Data was collected by 25 Businessman along with Bank managers, Principles of School and Head of Departments of University by structured survey to evaluate important aspects of emotional intelligence, such as self-awareness, emotion management, empathy, and social skills, alongside measures of managerial performance. The results show that there is positive relation with Emotional intelligence and effective management, managers with higher emotional intelligence tend to make better decisions, handle conflicts more effectively, manage teams well, and contribute to overall business success. Emotionally intelligent individuals are also better at managing stress, resolving workplace issues, and fostering a positive work environment, which helps improve employee performance and business outcomes. The research highlights the need for Emotional Intelligence training or programs in Pakistan and suggests that Emotional Intelligence Subject must be included in University Business Management Courses.